Measurement of jet shapes in top-quark pair events at √s = 7 TeV using the ATLAS detector - Alconada Verzini, María Josefina (2013)
A measurement of jet shapes in top-quark pair events using 1.8 fb−1 of √s = 7 TeV pp collision data recorded by the ATLAS detector at the LHC is presented. Samples of top-quark pair events are selected in both the single-lepton and dilepton final states. The differential and integrated shapes of the jets initiated by bottom-quarks from the top-quark decays are compared with those of the jets originated by light-quarks from the hadronic W-boson decays W →q¯q' in the single-lepton channel. The light-quark jets are found to have a narrower distribution of the momentum flow inside the jet area than b-quark jets.